THE INFLUENCE OF SERVICE QUALITY DIMENSIONS ON CUSTOMER SATISFACTION OF ISLAMIC PEOPLE'S FINANCING BANKS IN MEDAN CITY - Dhian Rosalina; Adelina Lubis; Ihsan Effendi (Jurnal Ekonomi, 2023)
This study aims to determine the effect of the dimensions of service quality consisting of reliability, responsiveness, assurance, empathy, and tangibles on customer satisfaction of sharia people's financing banks in the city of Medan. The sample in this study was 85 customers. The test tool used is Multiple Linear Regression, based on the results of research analysis there is a significant influence of service quality at Islamic People's Financing Banks in Medan City which consists of Reliability, Responsiveness, Assurance, Empathy, Tangibles on customer satisfaction of Islamic people's financing banks in Medan city